Not sure but I think she has 1 31/35 yards of ribbon.
Answer:
Arthur knows that there is a difference among the groups somewhere, but he does not know where
Step-by-step explanation:
An ANOVA test is a test to find out whether the results of an experiment or a survey are significant or not. ANOVA test helps the researcher or the experimenter to decide whether they reject the null hypothesis or accept the alternate hypothesis in the experiment. In ANOVA test, the experimenter wants to find if there is a difference between them or not.
In the context, Arthur is doing a study and he wishes to find out effect of a sleep deprivation on the number of the calories that people consumed. He collects some data from his subject group from the sleep lab and after running the ANOVA test, he finds out that he can reject the null hypothesis. So on this basis, Arthur knows that there is some basic difference among the members of the group somewhere, but he does not know where actually the difference is.
Answer:
Step-by-step explanation:
cos (x/2)=cos x+1
cos (x/2)=2cos ²(x/2)
2 cos²(x/2)-cos (x/2)=0
cos (x/2)[2 cos (x/2)-1]=0
cos (x/2)=0=cos π/2,cos (3π/2)=cos (2nπ+π/2),cos(2nπ+3π/2)
x/2=2nπ+π/2,2nπ+3π/2
x=4nπ+π,4nπ+3π
n=0,1,2,...
x=π,3π
or x=180°,540°,...
180°∈[0,360]
so x=180°
or
2cos(x/2)-1=0
cos (x/2)=1/2=cos60,cos (360-60)=cos 60,cos 300=cos (360n+60),cos (360n+300)
x/2=360n+60,360n+300
x=720n+120,720n+300
n=0,1,2,...
x=120,300,840,1020,...
only 120° and 300° ∈[0,360°]
Hence x=120°,180°,300°
The answer to your question is n is equal to 70
Answer:
Step-by-step explanation:
The given sequence of numbers is increasing in geometric progression. The consecutive terms differ by a common ratio, r
Common ratio = 6/3 = 12/6 = 2
The formula for determining the nth term of a geometric progression is expressed as
Tn = ar^(n - 1)
Where
a represents the first term of the sequence.
r represents the common ratio.
n represents the number of terms.
From the information given,
a = 3
r = 2
The function, f(n), representing the nth term of the sequence is
f(n) = 3 × 2^(n - 1)